NANOPARTÍCULAS DE Ag, Cu E Ag/Cu OBTIDAS PELO MÉTODO PVP: SÍNTESE, CARACTERIZAÇÃO E ESTUDO DA SUA APLICAÇÃO - Ianesko, Felipe (2016)
This work describes the synthesis of three different materials: i) silver nanoparticles ii) copper nanoparticles and iii) silver/copper nanoparticles. These three materials were obtained by synthetic method that use a common precursor, polyvinylpyrrolidone (PVP) and the precursor metallic salts, silver nitrate and copper sulfate. The samples were obtained from aqueous solutions of the precursors in acid medium and the synthesis involving copper particles were carried out in nitrogen atmosphere in order to avoid oxidation of copper to the respective oxides. The materials were characterized by different techniques such as Simultaneous Thermal Analysis (TG-DTA), UV-VIS Spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS) and Dynamic Light Scattering (DLS). The results obtained indicate that in the first synthesis, the metallic silver nanoparticles were obtained in the face centered cubic phase stabilized by PVP molecules, with an average particle size of 100 nm approximately. In the second synthesis (ii), metallic copper particles were obtained, however, by X-ray diffractometry was identified the presence of CuO in this sample. In an attempt to obtain the bimetallic particles, it was obtsined Cu in the three oxidation states: Cu0, and Cu2O and CuO oxides, indicating that further study of this synthesis conditions is necessary, in the last two cases. An electrochemical study of these materials was performed modifying a carbon paste electrodes, which confirmed that the materials presented electroactive character and showed better results when compared to non-modified electrodes. The electrode modified with silver nanoparticles shows interesting results for detection of escitalopran, this analysis showed inhibition of sensor behavior.